An Unintended Abolition - Anna Arons (Columbia Journal of Race and Law, 2022)
In a typical year, New York City’s vast family regulation system, fueled by an army of mandated reporters, investigates tens of thousands of reports of child neglect and abuse, policing almost exclusively poor Black and Latinx families even as the government provides those families extremely limited support. When the City shut down in the wake of the COVID-19 pandemic, this system shrunk in almost every conceivable way as mandated reporters retreated, caseworkers adopted less intrusive investigatory tactics, and family courts constrained their operations. Reports fell, the number of cases filed in court fell, and the number of children separated from their parents fell. At the same time, families found support elsewhere, through suddenly burgeoning mutual aid networks and infusions of new government entitlements. This large-scale reconfiguration of the family regulation system represents a short-term experiment in abolition: in this period, New Yorkers moved away from a system that oppressed poor Black and Latinx people and not only envisioned but built a more democratic and humane model to protect families.